Hepatic genomic assessment of dietary ingestion of 2-aminoanthracene in Sprague Dawley rats. Issue 3 (4th March 2023) - Cisse, Awa M.; Erber, Jody E.; McHale, Brittany J.; Gato, Worlanyo E.
Abstract: This research aims to investigate the effects of 2-aminoanthracene (2-AA), a polycyclic aromatic hydrocarbon (PAH), on the liver. PAH is a by-product of the incomplete combustion of fossil fuels. Specifically, the impact of 2-AA on different body tissues in animals has been reported. The liver is an organ central to the metabolism of PAHs, including 2-AA. Sprague Dawley rats ingested a well-defined dose of 2-AA in their diet (0, 50, and 100 mg/kg 2-AA) for 12 weeks. Hepatic global gene expression using Affymetrix Rat Genome 230 2.0 microarray was performed. Overall, more than 17, 000 genes were expressed. Approximately 70 genes were upregulated, while 65 were downregulated when control rats were compared with low-dose animals. Similarly, 103 genes were upregulated and 49 downregulated when the high-concentration 2-AA group was compared with the control group rats. This result suggests that the magnitude of gene expression fold change depends on the dose of 2-AA ingested. Several differentially expressed genes are involved in biological processes such as gene transcription, cell cycle, and immune system function, indicating that the ingestion of 2-AA could impact these processes. The over-expression of genes related to liver inflammation, nonalcoholic liver disease, hepatic glucose processing, and PAH metabolism were noted.